Music and identity : transformation and negotiation - Akrofi, E. A. (Eric Ayisi); Thorsén, Stig-Magnus; Smit, Maria (Sun Press, 2007)
Due to significant political and social changes over the last decade in their countries and worldwide, many scholars in the Nordic nations and in Southern Africa have been researching on ""music and identity""--An area with a paucity of literature. It is our hope that this book will be beneficial to scholars interested in the field of music and identity